logo for solving-math-problems.com
leftimage for solving-math-problems.com

Equation - Cant figure out how to rearrange the equation to solve for M










































Original equation is :

D= rt/6(3.14=pi)VN * cubed root of 4(pi)N/3Mu

need to get m= from the above equation and I am stuck. could yo show step by step how to solve for M.

thank-you

Comments for Equation - Cant figure out how to rearrange the equation to solve for M

Click here to add your own comments

Mar 17, 2012
Equation - solve for M
by: Staff


Question:

Original equation is:

D= rt/6(3.14=pi)VN * cubed root of 4(pi)N/3Mu

need to get m= from the above equation and I am stuck. could you show step by step how to solve for M.

thank-you



Answer:


D = rt/6(3.14=pi)VN * cubed root of 4(pi)N/3Mu

The notation used for the equation does not include enough parentheses. Parentheses show which parts of the equation should be grouped together.

However, two sections of the equation can be combined (regardless of where is parentheses should go), and considered as single variables.

1st part = rt/6(3.14=pi)VN

2nd part = cubed root of 4(pi)N


Once these changes have been made, the equation becomes:

D= (1st part) * (2nd part)/3Mu


The notation still leaves you with three possibilities

1st Possibility: D = (1st part) * (2nd part)*(1/3)*Mu

or

2nd Possibility: D = (1st part) * (2nd part)*[1/(3*M)]*u

or

3rd Possibility: D = (1st part) * (2nd part)*[1/(3*M*u)]


--------------------------------------------------

Solving for M:

1st Possibility: D= (1st part) * (2nd part)*(1/3)*Mu

D = (1st part) * (2nd part)*(1/3)*Mu

D / {(1st part) * (2nd part)*(1/3)} = {(1st part) * (2nd part)*(1/3)*Mu} / {(1st part) * (2nd part)*(1/3)*u}

D / {(1st part) * (2nd part)*(1/3)*u} = M

M = D / {(1st part) * (2nd part)*(1/3)*u}

>>> M = D / {( rt/6(3.14=pi)VN) * (cubed root of 4(pi)N)*(1/3)*u}


--------------------------------------------------

Solving for M:

2nd Possibility: D = (1st part) * (2nd part)*[1/(3*M)]*u

D = (1st part) * (2nd part)*[1/(3*M)]*u


D*M = {(1st part) * (2nd part)*[1/(3*M)]*u}*M

D*M = {(1st part) * (2nd part)*(1/3)*u}

D*M / D = {(1st part) * (2nd part)*(1/3)*u} / D

M = {(1st part) * (2nd part)*(1/3)*u} / D


>>> M = {(rt/6(3.14=pi)VN) * (cubed root of 4(pi)N)*(1/3)*u} / D


--------------------------------------------------

Solving for M:

3rd Possibility: D = (1st part) * (2nd part)*[1/(3*M*u)]

D = (1st part) * (2nd part)*[1/(3*M*u)]



D*M = {(1st part) * (2nd part)*[1/(3*M*u)]}*M

D*M = {(1st part) * (2nd part)*[1/(3*u)]}

D*M / D = {(1st part) * (2nd part)*[1/(3*u)]} / D

M = {(1st part) * (2nd part)*[1/(3*u)]} / D


>>> M = {( rt/6(3.14=pi)VN) * (cubed root of 4(pi)N)*[1/(3*u)]} / D




Thanks for writing.

Staff
www.solving-math-problems.com



Click here to add your own comments

Join in and write your own page! It's easy to do. How? Simply click here to return to Math Questions & Comments - 01.



Copyright © 2008-2015. All rights reserved. Solving-Math-Problems.com